QUALITY AND SUSTAINABILITY OF URBAN STREET LIGHTING: A STUDY OF WARRI (Nigerian Journal of Technology, 2016)
This paper presents the result of a study of the quality of Urban lighting. The purpose of installing the Street light is to light up all streets/roads in Warri at night. But due to some factors such as poles being brought down by accident or technical problem as a result of some bulbs that went bad without being replaced, the desired even lighting of the streets/roads was not always guaranteed.  This uneven lighting which results is a hazard to road users. We modeled the evenness of light on the roads and in the process captured the uneven lighting that a road user passing the roads will experience. The results of the model and the actual measurement of the Street light that was taken for some time, showed that parts of the roads experienced full, partial, one and three quarter lightings, while some other parts were thrown in complete darkness. The implication is that users travelling along the road experienced wide variation of light that could lead to accidents. For about two and half years after the study was conducted, the authors periodically monitored the conditions of the street lights to establish the extent of their sustainability. It was noticed that all the lights went off thereby returning the streets to their pre-lighting condition. The reason for the complete disruption is also reported as a learning point in project sustainability and a learning point for the future. http://dx.doi.org/10.4314/njt.v35i2.23